Pesantren Kaitan Struktural dan Pengalaman Historis - Sulistiono, Budi (Buletin Al-Turas, 2007)
The term of Pesantren (Islamic Boarding School) is not truly from Indonesia, nut adopted from India. Pesantren, Before the coming of colonial era such as (Portugal, Holland, England, and Japan) is the ones of Muslim educational institution in Nusantara. In the era of Colonialism, this institution is become the guardian of Islamic values and the spirits of Independency as seem at ulama's role in prtesting againts the enemy (Colonial Government).